High-performance all-polymer solar cells with only 0.47 eV energy loss - Wu, Qiang; Wang, Wei; Wang, Tao; Sun, Rui; Guo, Jing; Wu, Yao; Jiao, Xuechen; Brabec, Christoph; Li, Yongfang; Min, Jie (Science China-Chemistry, 2020)
The field of all-polymer solar cells (all-PSCs) has experienced rapid development during the past few years, mainly driven by the development of efficient polymer acceptors. However, the power conversion efficiencies (PCEs) of the all-PSCs are still limited by insufficient light absorption of the donor/acceptor blend and large energy loss in devices. We herein designed a polymer acceptor PYT1 constructed n-type molecular acceptor Y5-C20 as the key building block and blended it with a polymer donor PM6 to obtain an all-polymer photoactive layer. The optimized PM6:PYT1 all-PSCs achieved a record higher PCE of 13.43% with a very low energy loss of 0.47 eV and a photoresponse of up to 900 nm compared with the Y5-C20 based device with a best PCE of 9.42%. Furthermore, the PCEs of the PM6:PYT1 all-PSCs are relatively insensitive to the 1-chloronaphthalene (CN) additive contents and active layer thickness. Our results also highlight the effect of CN additive on PM6:PYT1 morphology, i.e., charge generation, and transport find an optimized balance, and radiative and non-radiative loss is simultaneously reduced in the blend. This work promotes the development of high-performance polymer acceptors and heralds a brighter future of all-PSCs for commercial applications.
CRIS-Team Scopus Importer:2020-07-17
Keywords: absorption coefficient; all-polymer solar cells; energy loss; mechanical stability; polymer acceptor